A Glowing Clot”: FDG PET/CT Identifies Persistent Tumour Thrombus in Metastatic Lung Carcinoma - Sana Munir Gill; Aimen Anis; Aimen Anis; Mairah Razi (Journal of the Pakistan Medical Association, 2025)
Tumour thrombi are a rare but serious complication of malignancy. It involves extension of organised collection of neoplastic cells into adjacent blood vessels, in contrast to a bland thrombus which consists of platelets and fibrin. It occurs more commonly in renal cell or hepatic cell carcinoma. Tumour thrombi are often asymptomatic and incidentally detected on imaging, however, their presence can affect staging, treatment options and prognosis of the patient. We present a rare case of a FDG avid tumour thrombus in left brachiocephalic vein in a patient with previously treated metastatic urothelial carcinoma and a second primary lung carcinoma. Keywords: Tumour thrombus, Urothelial carcinoma, FDG PET-CT, pulmonary adenocarcinoma